2010
DOI: 10.1179/174313209x414533
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection and enhanced neurogenesis by tetramethylpyrazine in adult rat brain after focal ischemia

Abstract: These results indicate that TMP could protect ischemic brain damage, and promote cell proliferation and differentiation stimulated by ischemia, which might be related to the reduction of nNOS expression after treatment with TMP in rat cerebral ischemia model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 34 publications
2
54
0
1
Order By: Relevance
“…Intraperitoneal administration of TMP was found to significantly protect the brain from ischemic insult, as shown by the reduction in infarction volume, neuronal loss, behavioral disturbance, and brain edema (Liao et al, 2004;Kao et al, 2006). TMP may provide neuroprotection against ischemia brain injury by inducing thioredoxin transcription (Zhu et al, 2009) or by reducing nNOS expression (Xiao et al, 2010). In addition, some studies have reported that TMP has protective effects against cardiovascular diseases and ischemia-reperfusion damage in the kidney (Dai, Bache, 1985;Zhou et al, 2004;Feng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal administration of TMP was found to significantly protect the brain from ischemic insult, as shown by the reduction in infarction volume, neuronal loss, behavioral disturbance, and brain edema (Liao et al, 2004;Kao et al, 2006). TMP may provide neuroprotection against ischemia brain injury by inducing thioredoxin transcription (Zhu et al, 2009) or by reducing nNOS expression (Xiao et al, 2010). In addition, some studies have reported that TMP has protective effects against cardiovascular diseases and ischemia-reperfusion damage in the kidney (Dai, Bache, 1985;Zhou et al, 2004;Feng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The neural nitric oxide synthase (nNOS) expression in the cortex and DG was reduced by TMP. These results indicate that TMP could protect brain from ischemic damage and promote cell proliferation and differentiation, which might be related to the reduction of nNOS expression (6). Using the ischemic model induced by oxygen glucose deprivation in vitro, Si et al (7) observed that Panax notoginseng saponins, with blood-activating and stasis-dissolving properties, could promote proliferation and differentiation of hippocampal NSCs by enhancing the expression of Nestin/BrdU and mRNA expressions of Tuj-1, vimentin, and nestin in hippocampal NSCs, which suggested its potential benefits on neural regeneration in cerebral ischemic injury.…”
Section: Action Of Anti-ischemic Brain Injurymentioning
confidence: 95%
“…손상 보호효능 [5][6][7][8] 과 in vivo의 뇌허혈 손상에 대해 매우 많은 연구가 이루어졌다 [9][10][11][12][13][14][15][16][17] . 또한 뇌출혈 18) 과 척수의 허혈과 압박 손상에 대해서도 유의한 효능이 있다고 하였다 [19][20][21][22] .…”
Section: Tetramethylpyrazine (Tmp)은 川芎 (Ligusticum Wallichii Franchatunclassified